Wyeth Pharmaceuticals : Premarin, Prempro and hormone replacement therapy (A) - Huang, Kathryn I. C.; Vanaelstyn, Megan E.; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
Millions of women worldwide between the ages of 45 and 55 experience the effects of menopause and have sought both treatment and relief in the form of hormone replacement therapy. Wyeth Pharmaceuticals, a division of Wyeth, Inc., is the market leader in prescription drug treatment for menopause with Premarin, a blend of natural estrogens (for women who have had a hysterectomy), and Prempro, a one-tablet hormone replacement therapy consisting of natural estrogens plus progestin. A stunning set of results from the Womens Health Initiative, released in the summer of 2002, however, challenges conventional approaches to treatment and poses a significant threat to Wyeth share price and market leadership.
Originally published: Huang, K. I. C., Vanaelstyn, M. E., & ORourke, J. S. (2003). Wyeth Pharmaceuticals: Premarin, Prempro and hormone replacement therapy (A). 03-05(A). Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Wyeth (Firm); Women's Health Initiative (U.S.); Pharmaceutical industry -- United States; Menopause -- Hormone therapy -- United States